POTENSI SUMBERDAYA KEPITING BAKAU (Scylla sp.) YANG DIPERDAGANGKAN DI KOTA TARAKAN, PROPINSI KALIMANTAN UTARA - Natanael, -; Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2016)
Tarakan city as center collected crab (Scylla sp.) that cacth from estuarine water area at North Kalimantan Province. The crabs for export have many kind size based on species, body complited, soft or hard the carapace, weight and eggs prosentase. The group category of crabs that found in trading Tarakan City have many variation name, They are H7, H5, H3, TG, CBH, CBK, % dan BS.Keywords : Crabs, Estuarine, Variation, North Kalimantan